Voronoi lattice-based orthotics with modular stiffness for additive manufacturing (Transactions on Additive Manufacturing Meets Medicine, 2022)
The additive manufacturing (AM) of soft polymers supports the creation of increasingly complex structures without molds. In the biomedical field, this also allows the manufacturing of customized devices based on the specific needs of each patient. This paper introduces the design and fabrication of orthotics, or orthopedic insoles, for the correction of abnormal pressure distributions at the plantar level. The solution provided is based on complex lattice structures with variable texture, able to adapt the local stiffness and the reaction force of the insole under the patient weight. Structural design methods are applied for the preliminary modeling of the device and the results validation by experiments. The struts stiffness are optimized by means of a finite element method (FEM) with imposed displacements and uniform pressure distribution target. The insole prototype is finally fabricated starting from the real pressure distribution of the patient, measured from its footprint.
Keywords: AM; orthotics; SLA; FEM; lattice; lightweight